Travel Writing as a Means for Colonialism: Reading Park’s Travel in the Interior Districts of Africa - Ghimire, Ram Prasad (Literary Studies, 2025)
This paper argues that since Euro-imperialism faced legitimation crisis in the late eighteenth century due to increasing rationalist and humanitarian ideologies, travel writing had to grow with a metaphorical use of sensibility to cover the grand design of colonialism in such situation. Mungo Park's narrative is characterized by the trope of sensibility for the same purpose. Being under the guardianship and protection of Joseph Banks, who was the president of the Royal Society and great designer of Britain's colonial expansion, Park tries to project himself in his narrative not as an ambitious and aggressive colonizer but an innocent genuine knowledge seeker.